The age of sustainable development - Sachs, Jeffrey D. (New York Columbia University Press, 2015)
"The Age of Sustainable Development is both sobering and inspiring: sobering because it presents in great detail the unprecedented challenges facing mankind; inspiring because it assures us that we can meet those challenges, if only we summon the will to act." - from book cover.
Introduction to sustainable development -- An unequal world -- A brief history of economic development -- Why some countries developed while others stayed poor -- Ending extreme poverty -- Planetary boundaries -- Social inclusion -- Education for all -- Health for all -- Food security -- Resilient cities -- Climate change -- Saving biodiversity and protecting ecosystem services -- Sustainable development goals.
Includes bibliographical references (pages [513]-519) and index.
Keywords: Sustainable development; Economic development -- Environmental aspects